Our Indigenous Ancestors : A Cultural History of Museums, Science, and Identity in Argentina, 1877-1943 - Larson, Carolyne R. (Carolyne Ryan), 1981- (Book collections on Project MUSE., 2015)
"Examines how museum anthropologists' scientific understandings of indigenous cultures during the nineteenth and twentieth centuries impacted creole Argentines' visions of national heritage and identity"--Provided by publisher